Physiotherapy intervention in Angola: what physicians think? - Leal, Edilson (2018)
Background: Physical therapy is an essential part of health systems. Physiotherapists can practice independent of other health professionals and also in the context of programs and interdisciplinary projects of habilitation/rehabilitation with the aim of giving function and quality of life in individuals with loss movement. There are guidelines for physiotherapists based on international standards issued by the World Confederation of Physical Therapy. (WCPT), what must be followed by physiotherapists globally. There are several health problems in Angola such as Malaria, stroke and traffic accidents that require physical therapy intervention in their rehabilitation process. Since doctors are professionals first contact in Angola responsible for referral of patients for physical therapy, it is pertinent to understand their awareness of the importance of the intervention of physiotherapists. Purpose: This study sought to investigate the perception of medical professionals in orthopedics, neurology and general practitioner of some hospital institutions in Luanda, Porto Amboim, Sumbe in Angola on the intervention of physiotherapists. Methods: The method used was quantitative descriptive and exploratory. The evaluation was conducted through a questionnaire response you close to 19 items, and the first part of the characterization of the sample (5 Items) and the second part consisting for items the advice of the doctors on the intervention of the physiotherapist in Angola (14 Items). The sample consisted of 38 doctors from orthopedists, neurologists and general practitioner in Luanda, Porto Amboim and Sumbe in Angola. For the analysis of the data was used IBM software Statistical Package for Social Sciences (SPSS statistics 20.0for Windows®). Results: The 38 individuals in the study 22 were male and 16 were female, Luanda is the city with the highest frequency of individuals who participated in the study, most are a general practitioner and worked in private clinics. Most believe that physiotherapists have a specific body of knowledge and can support their interventions. Most participants said that doctors have little knowledge of the professional physiotherapist role and not always refer their patients to physical therapy. The results of the study showed that neurologists and orthopedists have a perception of the greater importance of physiotherapy intervention. Conclusion(s): The doctors think it is important the intervention of the physiotherapist, and the three specialties orthopedics was considered as the one that needs more of the physiotherapist performance. Implications: This work can serve as an indicator of the view that doctors in Angola have of physiotherapists, can also serve to raise awareness of policies related to the integration of the physiotherapist in the multidisciplinary team in Angola.